Analisis Karakteristik Perilaku Perjalanan dan Willingness to Walk Penumpang BRT Trans Jateng (Purwokerto-Purbalingga) - Sari, Cremona Ayu Novita; Anjarwati, Sulfah; Afriandini, Besty (Proceedings Series on Physical & Formal Sciences, 2021)
The increasing need for transportation has prompted the government to provide public transportation to increase mobility and reduce the number of private vehicles. The Department of Transportation of Central Java Province has developed the Trans Jateng BRT (Bus Rapid Transit) mass transportation in the Barlingmascakeb area through activities to improve the Trans Jateng agglomeration transportation service. The BRT that has been operated in the Banyumas area is Corridor 1 on the Purwokerto-Purbalingga route. This study aimed to analyze the characteristics of travel behavior and passengers’ willingness to walk. The sampling of the research was random sampling using a questionnaire as the main data collection tool. The results of the discussion of travel behavior in terms of the purpose of the trip were dominated by recreation/shopping and education. The majority of BRT users used public transportation as the mode used before switching to BRT, the connecting mode from home to shelter is dominated by feeders, while from destination to shelter is dominated by walking. The connection distance from the house and from the destination to the shelter is >400 meters. Thus, the majority of respondents came from a buffer range of 0-400 meters. Based on willingness to walk, some respondents walk up to a radius of >400 meters. It is necessary to add more shelter points if the distance between stopping points does not meet the standards and provide better shelter access, especially by walking or using other integrated public transportation.